2012
DOI: 10.1159/000339330
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Telomeric DNA Sequences on the X-Radiation-Induced Chromosome Fragments Observed in the Genome of Androgenetic Brook Trout (<b><i>Salvelinus fontinalis</i></b>, Mitchill 1814)

Abstract: Cytogenetic screening of the androgenetic brook trout (Salvelinus fontinalis, Mitchill 1814) offspring hatched from eggs exposed to 420 Gy of X-radiation before insemination exhibited residues of the irradiated maternal nuclear genome in the form of small chromosome fragments. Remnants of the irradiated chromosomes had different sizes, and their number varied intraindividually from 1 to 15. To efficiently pass through the series of the cell divisions, such chromosome fragments must have had functional kinetoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Low doses of UV-and X-radiation applied to damage nuclear DNA in the spermatozoa and eggs resulted in the incomplete genetic inactivation of the brown trout gametes. Residues of the irradiated chromosomes may interfere with the cell cleavages and provoke consequent chromosome rearrangements what in turn may increase mortality among the doubled haploids (Ocalewicz et al 2012). Furthermore, genes from the radiation-induced chromosome fragments may contain mutated genetic information that is harmful for the haploid and doubled haploid individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Low doses of UV-and X-radiation applied to damage nuclear DNA in the spermatozoa and eggs resulted in the incomplete genetic inactivation of the brown trout gametes. Residues of the irradiated chromosomes may interfere with the cell cleavages and provoke consequent chromosome rearrangements what in turn may increase mortality among the doubled haploids (Ocalewicz et al 2012). Furthermore, genes from the radiation-induced chromosome fragments may contain mutated genetic information that is harmful for the haploid and doubled haploid individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Staining with 4′, 6-diamidino-2-phenylindole (DAPI) and the use of rDNA probes are major tools that are traditionally used to differentiate peanut chromosomes [ 5 8 ]. The application of centromeric and telomeric repeat probes has significantly improved the ability to resolve Arachis karyotypes [ 9 , 10 ]. Zhang et al [ 11 ] identified seven A. duranensis bacterial artificial chromosome (BAC) clones that facilitated the differentiation of almost all chromosomes of peanut.…”
Section: Introductionmentioning
confidence: 99%